Analysis of two-layered journal bearing lubricated with ferrofluid - Rao, T.V.V.L.N. (EDP Sciences, 2014)
The present study investigates the load capacity and friction coefficient for a two-layered journal bearing lubricated with ferrofluid. A modified Reynolds equation for a two-layered ferrofluid is derived using displaced infinitely long wire magnetic field model. Reynolds boundary conditions are used to obtain nondimensional pressure and shear stress expressions. Nondimensional load capacity and coefficient of friction are analyzed under the influence of lubricant layer's thickness, viscosities, magnetic field intensity and distance ratio parameter. Ferrofluid lubrication under the influence of magnetic field has potential to enhance load carrying capacity and reduce coefficient of friction for two-layered journal bearing. Â© 2014 Owned by the authors, published by EDP Sciences.